2016
DOI: 10.1021/jacs.6b03125
|View full text |Cite
|
Sign up to set email alerts
|

An Alkaline-Stable, Metal Hydroxide Mimicking Metal–Organic Framework for Efficient Electrocatalytic Oxygen Evolution

Abstract: Postsynthetic ion exchange of [Co2(μ-Cl)2(btta)] (MAF-X27-Cl, H2bbta =1H,5H-benzo(1,2-d:4,5-d')bistriazole) possessing open metal sites on its pore surface yields a material [Co2(μ-OH)2(bbta)] (MAF-X27-OH) functionalized by both open metal sites and hydroxide ligands, giving drastically improved electrocatalytic activities for the oxygen evolution reaction (an overpotential of 292 mV at 10.0 mA cm(-2) in 1.0 M KOH solution). Isotope tracing experiments further confirm that the hydroxide ligands are involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
304
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 479 publications
(321 citation statements)
references
References 51 publications
9
304
1
2
Order By: Relevance
“…[31] Herein, we report an in situ generated zeolite-Y-supported a-Co(OH) 2 film as aC o-OECw ith enormous stability and good efficiency.W er eport av ery simple but unique technique to generate at hin-film of a-Co(OH) 2 of a-Co(OH) 2 on the surface of zeolite-Y also remains the same. Moreover,t he efficiency of this heterogeneous electrocatalytic system is highert han for the existing, previously reported, aCo(OH) 2 -based electrocatalysts operating at alkalinep H. [29,30,32] Results and Discussion Figure 1c ompares 6 (Figure 1) matches well with that of previously reported Co II -exchanged zeolite-Y. [33] As shown in Figure 1, the relative intensities of the diffraction peaks at 10.1 and 11.88 are found to be reversed in Y-Co II (H 2 O) 6 .T his could be attributed to ac hange in the structure factor of zeolite-Y upon exchange with ar elatively heavier ion (Co II ), as has been reportedf or Cs I -exchanged zeolite-Y.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…[31] Herein, we report an in situ generated zeolite-Y-supported a-Co(OH) 2 film as aC o-OECw ith enormous stability and good efficiency.W er eport av ery simple but unique technique to generate at hin-film of a-Co(OH) 2 of a-Co(OH) 2 on the surface of zeolite-Y also remains the same. Moreover,t he efficiency of this heterogeneous electrocatalytic system is highert han for the existing, previously reported, aCo(OH) 2 -based electrocatalysts operating at alkalinep H. [29,30,32] Results and Discussion Figure 1c ompares 6 (Figure 1) matches well with that of previously reported Co II -exchanged zeolite-Y. [33] As shown in Figure 1, the relative intensities of the diffraction peaks at 10.1 and 11.88 are found to be reversed in Y-Co II (H 2 O) 6 .T his could be attributed to ac hange in the structure factor of zeolite-Y upon exchange with ar elatively heavier ion (Co II ), as has been reportedf or Cs I -exchanged zeolite-Y.…”
Section: Introductionmentioning
confidence: 78%
“…The zeolite support probably prevented the catalyst particles from agglomeration, thereby enhancing the activity as well as the long-term durability.W eh ave performed detailed electrochemical experiments to determine the oxygenevolution kinetics andf ound aT afel slope as low as 59 mV decade À1 at an overpotential of 329 mV with aT OF of 0.35 mol O 2 mol Co À1 s À1 at 1mAcm À2 in alkalinem edium (pH 13). Thus, the efficiency of this heterogeneous electrocatalytic system is superior to the existing a-Co(OH) 2 -based oxygenevolution electrocatalysts operating at alkalinep H. [29,30,32] Experimental Section Materials Sodium zeolite-Y was procured from Sigma-Aldrich (Molecular sieves, CAS No. 334 448, MDL No.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As such, one of the most challenging and rewarding endeavors in this field is to synthesize porous MOFs with good charge mobility and conductivity. Recently, the development of new type MOFs with enhanced intrinsic conductivity has attracted increasing attention 125, 126, 127. In 2009, Takaishi et al reported one of the first conductive MOFs, Cu[Cu(pdt) 2 ] (pdt = 2,3‐pyrazinedithiolate), and its electrical conductivity was 6 × 10 −4 S cm −1 at 300 K 128.…”
Section: Recent Advances In Mof‐based Catalysts For Water Splittingmentioning
confidence: 99%